Outcome Assessment and Impact Estimation: FTA's Research Contributions to Address Persistent Rural Poverty and Increasing Levels of Vulnerability (Challenge 4) - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
Poverty alleviation is an important focal area of scientific and applied research for FTA. FTA’s research tackles several drivers, including land-tenure insecurity, lack of education and government support to communities, yield and income vulnerability to climate change and market conditions, and lack of jobs or livelihoods. To help alleviate poverty, FTA conducted research to enhance coordination among multiple sectors to support favourable cross-sectoral policies for tree-planting and agroforestry development, produced and disseminated climate-smart and context-appropriate multi-species agroforestry systems to support optimal yields and livelihoods, and supported the realization of household’s economic potential from trees and agroforestry via value-chain development. FTA’s research also aims to address the compounding effects of unsustainable use of natural resources for livelihoods and cash income, such as climate change, damaged ecosystem services, land degradation, natural resource scarcity, food insecurity, and poor health. These drivers and effects serve as the entry points for FTA’s work.